2010
DOI: 10.4321/s1886-36552010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists´ attitude, perceptions and knowledge towards the use of herbal products in Abu Dhabi, United Arab Emirates

Abstract: ObjectiveThe purpose of the study was to assess pharmacists’ current practice, perception and knowledge towards the use of herbal products in Abu Dhabi, United Arab Emirates (UAE). The study assessed the need for incorporating herbal medicine as a separate topic in under- graduate pharmacy student curricula.MethodsThe study was done on 600 pharmacists employed in Abu Dhabi, who were contacted electronically, out of which 271 had completed the survey. The data was collected using a structured questionnaire.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 11 publications
(15 reference statements)
8
35
2
Order By: Relevance
“…Pharmacists reported high sales of registered HMs at their community pharmacies, which is similar to what was reported in the UAE [13] and Palestine [14]. Pharmacists believe that Jordanians use HMs due to beliefs in their safety and efficacy.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Pharmacists reported high sales of registered HMs at their community pharmacies, which is similar to what was reported in the UAE [13] and Palestine [14]. Pharmacists believe that Jordanians use HMs due to beliefs in their safety and efficacy.…”
Section: Discussionsupporting
confidence: 69%
“…Revising the existing local pharmacy curriculum and providing training for pharmacy graduates on clinical phytotherapy is recommended [13]. Fortunately, this is the case in Jordan, as most practicing pharmacists in the community setting receive extensive education in this domain at the undergraduate B.Pharm and Pharm.D degree levels [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This questionnaire is designed to draw conclusions about the behavior and target of using herbs and herbal medicines by students of health sciences (Dentistry and Pharmacy) in a university in UAE 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This study will, also, explore antibiotics dispensing patterns as many studies done in UAE reported that dispensing antibiotics as an over the counter medications is a relatively frequent problem [1,2]. In addition, a limited published data is available about the provision of pharmaceutical care in community pharmacies in the UAE [3]. Almost no documentation of efforts was taking place in community pharmacy [4].…”
Section: Introductionmentioning
confidence: 99%